ELECTROPHILIC AND NUCLEOPHILIC CHEMICAL REACTIVITY OF NEUTRAL AND ANIONIC FORMS OF 4-CPA, 24D-CPA, 34-CPA AND 245T-CPA THROUGH CONCEPTUAL DFT REACTIVITY DESCRIPTORS - Mendoza-Huizar, L. H.; Rios-Reyes, C. H.; Álvarez-Romero, G. A.; Palomar-Pardavé, M. E.; Ramírez-Silva, M. T. (Journal of the Chilean Chemical Society, 2017)
In the present work, we have analyzed the electrophilic and nucleophilic chemical reactivity of the neutral and anionic chlorophenoxyacetic acid herbicides, 4-CPA, 24D-CPA, 34-CPA and 245T-CPA at the X/6-311++G(2d,2p) level of theory (where X= wB97XD, MPW91B1K and MP2). Chemical reactivity was analyzed in the aqueous phase and employing global and local DFT reactivity descriptors. The structural parameters derived from DFT calculations are equivalent to those obtained at the MP2 level. The Fukui Function values suggest that nucleophilic attacks to the neutral and anionic forms would cause dechlorination on 24D-CPA, 34-CPA and 245T-CPA and hydrogen abstraction in 4-CPA. At pH values lower than 2.7, electrophilic attacks would cause the cleavage of the ether bond in 4-CPA, 24D-CPA and 34-CPA and dechlorination in 245T-CPA. But, at pH > 3.6, electrophiles may cleave the ether bond to start the degradation of the four CPAs.